Prevalence of Depression and Its Associated Factors Among Patients Undergoing Substance Abuse Treatment at Rehabilitation Centres in Pokhara, Nepal - Avinash Adhikari; Kusumsheela Bhatta; Sagar Parajuli; Hari Prasad Kaphle (Mental Illness)
Depression and substance use disorders (SUDs) pose a substantial global health burden, impacting both individual’s well-being and societal functioning, as well as economic stability. The co-occurrence of these conditions within rehabilitation centres further complicates treatment outcomes and recovery trajectories. The objective of this study was to identify the prevalence and factors associated with depression among patients undergoing substance abuse treatment in rehabilitation centres located in Pokhara Metropolitan City of Nepal. An institution-based cross-sectional study was done to conduct the research among rehabilitation centre patients in Pokhara Metropolitan. A multistage probability sampling approach was used to select 212 patients who were admitted to rehabilitation centres. Data collection utilized a semistructured questionnaire administered through face-to-face interviews. The collected data were entered into EpiData software and analysed using SPSS. Binary logistic regression using odds ratios with a 95% confidence interval was performed. In total, 212 participants were interviewed, with more than half (58%) of the patients in the rehabilitation centre experiencing depression. Among them, 47.2% exhibited mild depression, 9.9% had moderate depression, and 1.4% experienced severe depression. Factors significantly associated with depression (p<0.05) were financial capabilities (UOR=2.71), sleep duration (UOR=2.16), problematic sleep (UOR=3.19), violence exposure (UOR=3.12), and self-esteem (UOR=2.06). The study identified a high prevalence of depression among patients undergoing substance abuse treatment in rehabilitation centres. The findings highlight the importance of implementing comprehensive measures within rehabilitation centres, including the introduction of financial support programs, sleep hygiene education, violence prevention strategies, and self-esteem enhancement approaches.